Combining Banking with Private Equity Investing - Fang, Lily; Ivashina, Victoria; Lerner, Josh (Review of Financial Studies, 2013)
Bank-affiliated private equity groups account for 30% of all private equity investments. Their market share is highest during peaks of the private equity market, when the parent banks arrange more debt financing for in-house transactions yet have the lowest exposure to debt. Using financing terms and ex post performance, we show overall that banks do not make superior equity investments to those of stand-alone private equity groups. Instead, they appear to expand their private equity engagement to take advantage of the credit market booms, while capturing private benefits from cross-selling of other banking services.